2020
DOI: 10.1590/fst.32619
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and antioxidant effects of grape processing by-products in high-fat/cholesterol diet-induced hyperlipidemic hamsters

Abstract: Investigations have shown the presence of bioactive substances in agricultural by-products. As some of these compounds present hypolipidemic and antioxidant activities, they could be considered economical alternatives to be used as supplements. This study investigates the hypolipidemic and antioxidant properties of grape processing by-products, feeding them to hamsters for 28 days. Wine pomace flour and grape juice pomace flour proved to have substantial amounts of fibers and phenolic compounds, both recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The effects of grape polyphenols on lipid metabolism remain controversial. The mechanism by which they may positively modify lipid profiles may be associated with the flavonoid fraction and their capacity to reduce the absorption of dietary fat in the intestine, decreasing postprandial chylomicron concentrations [ 33 , 34 ]. It has also been reported that proanthocyanidins inhibit hepatic VLDL secretion, reduce plasma lipids and increase beta-oxidation [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of grape polyphenols on lipid metabolism remain controversial. The mechanism by which they may positively modify lipid profiles may be associated with the flavonoid fraction and their capacity to reduce the absorption of dietary fat in the intestine, decreasing postprandial chylomicron concentrations [ 33 , 34 ]. It has also been reported that proanthocyanidins inhibit hepatic VLDL secretion, reduce plasma lipids and increase beta-oxidation [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a beverage composed by tropical fruits and yacon showed antioxidant and prebiotic effects on alloxan-induced diabetic rats, which contains high levels of fructooligosaccharides, gallic acid and ascorbic acid (Dionisio et al, 2020). Grape processing by-products have substantial amounts of fibers and phenolic compounds had hypolipidemic and antioxidant effects on high-fat/cholesterol diet-induced hyperlipidemic hamsters (Ishimoto et al, 2020). VD is mainly derived from animal foods such as animal liver, cod-liver oil, yolk and cream.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS production is also one of the mechanisms leading to ischemia/reperfusion-induced cellular injury (Blokhina et al, 2003). The MDA level is one of Nrf2 is an antioxidant transcription factor that plays a key role in resisting oxidative stress caused by various stress environments (Ishimoto et al, 2020). Nrf2 is an endogenous antioxidant defense system and could maintain cellular homeostasis under stress conditions (Fetoni et al, 2015).…”
Section: Discussionmentioning
confidence: 99%